The Peculiarities of Conducting Special Operational-Search Measures in the Fight Against Crime - Madiev, K.S.; Koszhanov, T.A.; Shaimuhanov, A.D.; Filin, V.V. (International Journal of Criminology and Sociology, 2021)
The relevance of the study is due to the need to determine the feasibility of using special operational-search measures in the system of operational-search activities of the authorized bodies of Kazakhstan and to establish their place and importance in the fight against crime. In this regard, this article is aimed at identifying and disclosing the essence of operational search activities, identifying their main content. A comparative study of the legislation of individual countries providing for similar activities was carried out in order to identify the features of the conduct and the legal regulation of operational search activities and their significance. As a result of the study, it was concluded that the features of special operational-search measures are manifested only in their number, name, and partly in the content of the actions taken, while their essence is manifested almost equally. Along with this, to ensure the reliability of the results obtained, scientific and technical means are being actively introduced, mechanisms and methods for recording operational information are being improved, and scientific knowledge is being accumulated and well-grounded recommendations for conducting operational-search measures. The materials of the article are of practical value for the bodies that carry out operational investigative activities, scientific and practical workers of the authorized bodies.